Comparative study for microstructural characterisations and properties of Ti-Y powders produced by vacuum induction gas atomization cold crucible process. (20th October 2021) - Kim, Dae-Kyeom; Kim, Young Il; Kim, Young Do; Lee, Dongju; Lee, Bin; Kim, Taek-Soo
ABSTRACT: Ti-based alloy powder is an excellent candidate as an additive manufacturing material, owing to its high strength-to-weight ratio, corrosion resistance and biocompatibility. However, molten Ti is highly reactive with ceramic crucibles. Thus, only crucible-free techniques can be used, limiting the manufacturing. In this study, Ti–Y, CP-Titanium powder was manufactured using the vacuum induction gas atomization cold crucible (VIGA-CC) process, without using any master alloy; moreover, its properties were elucidated. Characterisations were performed to comparatively analyse the surface morphology, impurity content and mechanical properties of the synthesised powder. It was found that the powder had a uniform composition and was refined by the yttrium addition. The VIGA-CC process, by which alloy powders with various compositions can be prepared, is expected to expand the list of target alloys that can be used in additive manufacturing processes.